The Influence of Learning Leadership, Educational Administration Knowledge, Job Satisfaction and Work Motivation on Organizational Commitment of the Head of the Early Childhood Education (ECE) Units in Medan City - Kristianus Mote; Benyamin Situmorang; Darwin (International Journal of Science, Technology & Management, 2021)
The purpose of this study is (1) to find a model of organizational commitment of the head of the ECE unit which is built based on an associative causal relationship between exogenous variables with an endogenous variable. (2) to test and find direct and indirect effects between exogenous variables with an endogenous variable. This study used a quantitative method with a survey approach. The population was 750 people, and the samples were 238 people. They were collected using a purposive sampling technique based on the sample provisions by Isaac and Michael. Data were collected using questionnaires in the form of a Likert Scale technique with a Merriam technique test instrument. The data were processed using a Path Analysis. The results of the analysis show that (1) the direct influence of learning leadership on the organizational commitment of the head of the ECE units with a path coefficient of 0,119. (2) the direct influence of education administration knowledge on the organizational commitment of the head of the ECE units with a path coefficient of 0,406. (3) the direct influence of job satisfaction on the organizational commitment of the head of the ECE units with a path coefficient of 0,369. (4) the direct influence of work motivation on the organizational commitment of the head of the ECE units with a path coefficient of 0,175. The conclusion is that the organizational commitment model of the head of the ECE units in Medan City has been tested fit with proportional direct and indirect, spurious and unanalyzed effects with a dominant proportional influence that is (1) education administration knowledge of 26,42. (2) job satisfaction of 13,60%. (3) work motivation of 03,06%. (4) learning leadership is 01,41%. The suggestion is that if you want to increase the organizational commitment of the head of the ECE units, it is necessary to first increase the knowledge of educational administration and then be followed by job satisfaction, work motivation and learning leadership.